Dustproof self-cleaning coating and preparation method thereof
By modifying dust-proof self-cleaning coatings combined with graphene oxide and silicone resin, the problem of the decrease in power generation efficiency of photovoltaic glass in polluted areas is solved, and the self-cleaning effect and cost reduction are achieved.
Patent Information
- Application Number
- CN202411537776.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
Photovoltaic glass surface dust and dirt in areas with high pollution or wind and sand lead to a decrease in power generation efficiency, and the existing cleaning methods are costly and strong.
A dust-proof self-cleaning coating is provided, including components A, components B and components C. By combining modified graphene oxide with silicone resin, a coating with antistatic properties and self-cleaning effect is formed.
This coating can effectively prevent dust from adsorbing on photovoltaic modules, extend service life, reduce cleaning costs, and improve power generation efficiency.
Smart Images

Figure CN119410247A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of self-cleaning materials, and in particular relates to a dustproof self-cleaning coating and a preparation method thereof. Background Art
[0002] As one of the clean, efficient and inexhaustible green energy technologies of the future, solar energy technology has been increasingly widely used in recent years, and the solar photovoltaic glass industry, a product that combines solar energy utilization with the traditional glass industry, is becoming one of the fastest growing high-tech industries in the world and is known as an emerging sunrise industry. In recent years, the photovoltaic power generation industry has developed rapidly, the installed capacity has experienced explosive growth, and distributed photovoltaic power generation has also developed rapidly. In particular, it is encouraged and advocated to use the roofs of residential buildings and factory buildings to install distributed grid-connected photovoltaic power generation models.
[0003] However, in areas with heavy pollution or sandstorms, dust and dirt on the surface of photovoltaic glass will significantly reduce the average photovoltaic power generation efficiency. If it is not cleaned for a long time, regional dirt will form on the surface of photovoltaic glass, and the power generation will be reduced by more than 10%. The current cleaning methods include manual dry cleaning, manual water washing, engineering vehicle cleaning equipment and intelligent component cleaning robots, but there are problems such as high cost and high intensity. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a dust-proof self-cleaning coating and a preparation method thereof, aiming to provide a self-cleaning coating to reduce the technical problems of low power generation efficiency and high cleaning cost.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides the following technical solution: a dustproof self-cleaning coating, the self-cleaning coating comprising component A, component B and component C;
[0007] The component A comprises the following components in terms of weight percentage: 60%-70% of silicone resin, 1%-5% of graphene oxide, 10%-15% of dispersant, and 5%-8% of polyethylene glycol antistatic agent;
[0008] The B component comprises the following components according to weight percentage: 40%-60% polyurethane and 1%-5% silane coupling agent;
[0009] The C comprises the following components according to weight percentage: 60%-70% of base resin, 1%-5% of organic tin catalyst, 10%-12% of polyethylene glycol antistatic agent, 2%-8% of boron nitride, and 6%-10% of graphene oxide;
[0010] The liquid viscosity of the polyurethane is 200-800 cps; the base resin is an aliphatic polyester resin with a hydroxyl value of 150-180 mgKOH / g; the particle size of the graphene oxide in the A component is 10-20 microns; and the particle size of the graphene oxide in the C component is 50-100 microns.
[0011] Furthermore, the mass ratio of the component A, the component B, and the component C is: (1:5)-(6:8)-(1:3).
[0012] Furthermore, the base resin is polymerized by aliphatic polybasic acid mixture and polyol mixture under the action of an organic tin catalyst.
[0013] Furthermore, the silane coupling agent is one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.
[0014] Furthermore, the dispersant is at least one of 2,2-bis(4-hydroxyphenyl)propane polycarbonate, sodium 3-trimethylsilyl-1-propanesulfonate, and N-carbamoylmethylethanesulfonic acid.
[0015] A method for preparing a dustproof self-cleaning coating, characterized in that it includes using the photovoltaic dustproof self-cleaning coating as described above, and the preparation method includes the following steps:
[0016] S01: Ultrasonic dispersion of silicone resin, graphene oxide, polyethylene glycol antistatic agent and dispersant in anhydrous ethanol to form a mixture A;
[0017] S02: dissolving polyurethane and silane coupling agent in anhydrous ethanol to form a mixture B;
[0018] S03: stirring and dissolving the basic resin and the organotin catalyst in propanol, and standing for 3-4 hours; then adding the polyethylene glycol type antistatic agent, boron nitride, and graphene oxide and mixing evenly to form a mixture C;
[0019] S04: uniformly mixing mixture A, mixture B and mixture C by ultrasonic dispersion, filtering, washing and drying to obtain mixture D;
[0020] S05: Apply the mixture D to the surface of the photovoltaic module and dry it at room temperature for 14-16 hours to obtain a self-cleaning coating.
[0021] Furthermore, the step S03 includes:
[0022] A. Stir and dissolve the basic resin and organotin catalyst in propanol and let stand for 3 hours;
[0023] B. Then, add polyethylene glycol antistatic agent, boron nitride and graphene oxide at a concentration of 40-50 mg / mL to step A, stir for 4-6 hours, separate the solid and liquid, and dry to form a mixture C.
[0024] Furthermore, the preparation of the graphene oxide comprises the following steps:
[0025] Graphene is added to a mixture of hydrogen peroxide and sodium borate, and reacted for 20 to 60 minutes in an ice bath at a temperature below 10-15° C. to obtain preliminary graphene oxide. The temperature is then raised to 30° C., potassium permanganate is added, and reacted for 20 to 50 minutes to obtain graphene oxide.
[0026] The beneficial effects of the present invention are as follows: compared with the prior art, the dust-proof self-cleaning coating of the present invention has the following advantages:
[0027] (1) By using an organic silicon resin material as a carrier, using a polyethylene glycol type antistatic agent to modify graphene oxide, and grafting polyethylene glycol onto graphene oxide, on the one hand, the interlayer spacing of graphene oxide can be extended, which helps to inhibit the aggregation of graphene oxide, and on the other hand, the compatibility of graphene oxide and organic silicon resin is improved; by using a dispersant, the modified graphene oxide can be better dispersed in the silicone resin. At the same time, the use of modified graphene oxide ensures that it will not gradually seep out during use, so that the formed coating has permanent antistatic properties, avoids dust adsorption on photovoltaic modules, extends the service life of the coating, and reduces the cost of frequent replacement of the coating;
[0028] (2) The matrix resin can make the coating have good UV aging resistance, thereby improving the outdoor durability and service life of the coating; by using polyethylene glycol type antistatic agent to modify graphene oxide, the formed coating has antistatic properties, which repels dust in the air, so that dust cannot fall on the coating, thereby achieving a self-cleaning effect; the boron nitride sheet structure is connected with the modified graphene oxide, thereby forming a certain three-dimensional spatial network structure; it is conducive to placing modified graphene oxide with smaller particle size in it, and by using modified graphene oxide with different particle sizes for matching, a synergistic effect is generated between the fillers, thereby helping to improve the self-cleaning effect of the photovoltaic device;
[0029] (3) The difference in content density between the graphene oxide in component A and the graphene oxide in component B helps to avoid the diffusion and migration of the modified graphene oxide to the outer layer under the action of ultraviolet light, heat generated by light, etc., which helps to improve the stability of the microstructure of the coating and enhance the service life of the coating;
[0030] (4) By using polyurethane with higher viscosity and silane coupling agent, the hydroxyl and carboxyl groups in the base resin have higher activity and can react with the silane coupling agent, which can increase the cross-linking density of the coating, enhance the bonding strength of each component, and extend the service life of the coating.
[0031] In the present application, the coating formed by the synergistic effect of the above components has good durability and antistatic properties. The formed coating is applied to photovoltaic modules, thereby greatly reducing the cleaning cost and improving the efficiency of power generation.
[0032] Other advantages, objectives and features of the present invention will be described in the following description and will be apparent to those skilled in the art to some extent, or those skilled in the art may be taught from the practice of the present invention. The objectives and other advantages of the present invention may be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:
[0034] Figure 1 A flow chart of a method for preparing a dust-proof self-cleaning coating according to an embodiment of the present invention;
[0035] Figure 2 A flowchart of step S03 is provided for one embodiment of the present invention. DETAILED DESCRIPTION
[0036] This embodiment provides a dustproof self-cleaning coating, which includes component A, component B and component C;
[0037] The component A comprises the following components in terms of weight percentage: 60%-70% of silicone resin, 1%-5% of graphene oxide, 10%-15% of dispersant, and 5%-8% of polyethylene glycol antistatic agent;
[0038] The B component comprises the following components according to weight percentage: 40%-60% polyurethane and 1%-5% silane coupling agent;
[0039] The C comprises the following components according to weight percentage: 60%-70% of base resin, 1%-5% of organic tin catalyst, 10%-12% of polyethylene glycol antistatic agent, 2%-8% of boron nitride, and 6%-10% of graphene oxide;
[0040] The liquid viscosity of the polyurethane is 200-800 cps; the base resin is an aliphatic polyester resin with a hydroxyl value of 150-180 mgKOH / g; the particle size of the graphene oxide in the A component is 10-20 microns; and the particle size of the graphene oxide in the C component is 50-100 microns.
[0041] In the present application, by using an organic silicon resin material as a carrier, using a polyethylene glycol type antistatic agent to modify graphene oxide, and grafting polyethylene glycol onto graphene oxide, on the one hand, the interlayer spacing of graphene oxide can be extended, which helps to inhibit the aggregation of graphene oxide, and on the other hand, the compatibility of graphene oxide with organic silicon resin is improved; by using a dispersant, the modified graphene oxide can be better dispersed in the silicone resin. At the same time, the use of modified graphene oxide ensures that it will not gradually seep out during use, so that the formed coating has permanent antistatic properties, avoids dust adsorption on photovoltaic modules, extends the service life of the coating, and reduces the cost of frequent replacement of the coating; the base resin can make the coating have good UV aging resistance, improve the outdoor durability and service life of the coating; by using a polyethylene glycol type antistatic agent to modify graphene oxide, the formed coating has antistatic properties, and generates dust in the air. Repel, so that dust cannot fall on the coating, and play a self-cleaning effect; connect the boron nitride sheet structure with the modified graphene oxide, so as to form a certain three-dimensional spatial network structure; it is conducive to the placement of modified graphene oxide with smaller particle size, and by using modified graphene oxide with different particle sizes for matching, a synergistic effect is generated between the fillers, which helps to improve the self-cleaning effect of the photovoltaic component; through the content density difference between the graphene oxide in the A component and the graphene oxide in the B component, it helps to avoid the diffusion and migration of the modified graphene oxide to the outer layer under the action of ultraviolet light, heat generated by light, etc., which helps to improve the stability of the microstructure of the coating and enhance the service life of the coating; by using polyurethane with higher viscosity and silane coupling agent, the hydroxyl and carboxyl groups in the matrix resin have higher activity and can react with the silane coupling agent, which can increase the crosslinking density of the coating, enhance the bonding strength of each component, and extend the service life of the coating. Through the synergistic effect of the above components, the coating formed has good durability and antistatic properties, and the formed coating is applied to photovoltaic modules, thereby greatly reducing the cost of cleaning and improving the efficiency of power generation.
[0042] Preferably, the liquid viscosity of the polyurethane is 200-800cps. Specifically, the liquid viscosity may be 200cps, 300cps, 400cps, 500cps, 600cps, 700cps, 800cps. In the present application, the liquid viscosity of the polyurethane is preferably 600cps, which has the best compatibility with the above components and is easy to adjust the hydrophobicity.
[0043] Preferably, the graphene oxide particle size in the A component may be 10 microns, 12 microns, 14 microns, 16 microns, 18 microns, 20 microns, etc. Of course, in the present application, the graphene oxide particle size in the A component may also be set to other values, which are not limited here.
[0044] Preferably, the graphene oxide particle size in the B component may be 50 microns, 60 microns, 70 microns, 80 microns, 90 microns, 100 microns, etc. Of course, in the present application, the graphene oxide particle size in the C component may also be set to other values, which are not limited here.
[0045] In the present application, the mass ratio of component A, component B and component C is (1:5)-(6:8)-(1:3), for example, it can be 1:6:1, 2:7:2, 4:7:2, etc.
[0046] In the present application, the base resin is polymerized by aliphatic polyacid mixture and polyol mixture under the action of organic tin catalyst. Since aliphatic polyester resin is used to replace the commonly used aromatic polyester resin, the coating has better UV resistance and anti-aging properties.
[0047] Preferably, the silane coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.
[0048] Table 1 Examples 1-6 show the composition ratios of the self-cleaning coatings
[0049] Component A Component B C Component Example 1 1 6 1 Example 2 2 6 1 Example 3 2 7 2 Example 4 2 7 3 Example 5 3 8 3 Example 6 4 8 3
[0050] Note: The above components are measured according to mass fraction, that is, the mass ratio base can be determined in advance, such as 2g, 4g, 6g, etc. For example, taking 2g as an example, "1" in Table 1 represents 2g, "2" represents 4g, and so on. It will not be repeated here.
[0051] Table 2 Performance test results shown in Examples 1-6
[0052] Antifouling dust-proof Water resistance Save time Example 1 better better No abnormality 10 months Example 2 very good better No abnormality 10.5 months Example 3 very good good No abnormality 12 months Example 4 very good very good No abnormality 13 months Example 5 very good very good No abnormality 25 months Example 6 very good very good No abnormality 30 months
[0053] According to the performance test table of Examples 1-6 in Table 2 above, it can be seen that in the present invention, by comparing Example 1 with Example 2, it can be seen that with the increase of the content of component A, its anti-fouling effect is significantly enhanced, which is due to the increase in the content of modified graphene oxide; by comparing Example 2 with Example 3, with the increase of the content of component C, the storage time and dustproof effect are slightly enhanced, and by comparing Example 4, Example 5, and Example 6, it can be seen that with the further increase of the content of component C, the dustproof effect and storage time are significantly enhanced, and the prepared self-cleaning coating has higher waterproof, oil-proof, dust-proof, and durability effects.
[0054] In this application, please refer to Figure 1 As shown, a method for preparing a dustproof self-cleaning coating is also disclosed, including using the photovoltaic dustproof self-cleaning coating as described above, and the preparation method includes the following steps:
[0055] S01: Ultrasonic dispersion of silicone resin, graphene oxide, polyethylene glycol antistatic agent and dispersant in anhydrous ethanol to form a mixture A;
[0056] S02: dissolving polyurethane and silane coupling agent in anhydrous ethanol to form a mixture B;
[0057] S03: stirring and dissolving the basic resin and the organotin catalyst in propanol, and standing for 3-4 hours; then adding the polyethylene glycol type antistatic agent, boron nitride, and graphene oxide and mixing evenly to form a mixture C;
[0058] S04: uniformly mixing mixture A, mixture B and mixture C by ultrasonic dispersion, filtering, washing and drying to obtain mixture D;
[0059] S05: Apply the mixture D to the surface of the photovoltaic module and dry it at room temperature for 14-16 hours to obtain a self-cleaning coating.
[0060] In the present application, the modified graphene oxide can be well dispersed in the silicone resin by ultrasonic treatment at room temperature for 3-4 hours; the basic resin and the organotin catalyst are stirred and dissolved in propanol, and left to stand for 3-4 hours to form a fatty acid resin with high activity; the polyurethane and the silane coupling agent are dissolved in anhydrous ethanol to form a mixture B, and the mixture A and the mixture C are ultrasonically dispersed and mixed uniformly, filtered, washed, and dried to obtain a mixture D; the mixture D is applied to the surface of the photovoltaic module and dried at room temperature for 14-16 hours to obtain a self-cleaning coating. Through the synergistic effect of the above components, the coating formed has good durability and antistatic properties, and the formed coating is applied to the photovoltaic module, thereby greatly reducing the cost of cleaning and improving the efficiency of power generation.
[0061] For further information, see Figure 2As shown, step S03 includes:
[0062] A. Stir and dissolve the basic resin and organotin catalyst in propanol and let stand for 3 hours;
[0063] B. Then, add polyethylene glycol antistatic agent, boron nitride and graphene oxide at a concentration of 40-50 mg / mL to step A, stir for 4-6 hours, separate the solid and liquid, and dry to form a mixture C.
[0064] In the present application, aliphatic polyester resin is prepared in advance by stirring a basic resin with an organic tin catalyst, replacing the commonly used aromatic polyester resin, so that the coating has better UV resistance and anti-aging properties; then, a polyethylene glycol-type antistatic agent, boron nitride, and graphene oxide are added to form a stable three-dimensional network structure, and small-particle graphene oxide can be accommodated therein, so that the formed coating has antistatic properties, repels dust in the air, prevents dust from falling on the coating, and has a self-cleaning effect.
[0065] Furthermore, the preparation of the graphene oxide comprises the following steps:
[0066] Graphene is added to a mixture of hydrogen peroxide and sodium borate, and reacted for 20 to 60 minutes in an ice bath at a temperature below 10-15° C. to obtain preliminary graphene oxide. The temperature is then raised to 30° C., potassium permanganate is added, and reacted for 20 to 50 minutes to obtain graphene oxide.
[0067] In this application, the addition of modified graphene is mainly to improve the overall antistatic properties. In the processing of modified graphene, it is first oxidized by hydrogen peroxide and sodium borate. Hydrogen peroxide is a common oxidant and is often used for oxidation, while the addition of sodium borate is mainly to adjust the oxidation intensity, prevent over-oxidation, and make the initial oxidation more uniform. Over-oxidation will cause it to lose the properties that graphene itself has. In addition, after the initial oxidation, potassium permanganate is added for re-oxidation, so that the pores of the graphene oxide finally oxidized are more uniform.
[0068] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A dustproof self-cleaning coating, characterized in that: The self-cleaning coating comprises component A, component B and component C; The component A comprises the following components in terms of weight percentage: 60%-70% of silicone resin, 1%-5% of graphene oxide, 10%-15% of dispersant, and 5%-8% of polyethylene glycol antistatic agent; The B component includes the following components according to weight percentage: 40%-60% polyurethane and 1%-5% silane coupling agent; The C comprises the following components according to weight percentage: 60%-70% of base resin, 1%-5% of organic tin catalyst, 10%-12% of polyethylene glycol antistatic agent, 2%-8% of boron nitride, and 6%-10% of graphene oxide; The liquid viscosity of the polyurethane is 200-800 cps; the base resin is an aliphatic polyester resin with a hydroxyl value of 150-180 mgKOH / g; the particle size of the graphene oxide in the A component is 10-20 microns; and the particle size of the graphene oxide in the C component is 50-100 microns.
2. The dustproof self-cleaning coating according to claim 1, characterized in that: The mass ratio of the A component, the B component, and the C component is: (1:5)-(6:8)-(1:3).
3. The dustproof self-cleaning coating according to claim 1, characterized in that: The base resin is polymerized by aliphatic polybasic acid mixture and polyol mixture under the action of organic tin catalyst.
4. The dust-proof self-cleaning coating according to claim 1, characterized in that: The silane coupling agent is one of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane and γ-methacryloxypropyl trimethoxysilane.
5. The dust-proof self-cleaning coating according to claim 1, characterized in that: The dispersant is at least one of 2,2-bis(4-hydroxyphenyl)propane polycarbonate, sodium 3-trimethylsilyl-1-propanesulfonate, and N-carbamoylmethylethanesulfonic acid.
6. A dustproof self-cleaning coating, characterized in that: The method comprises using the dustproof self-cleaning coating according to any one of claims 1 to 5, and the preparation method thereof comprises the following steps: S01: Ultrasonic dispersion of silicone resin, graphene oxide, polyethylene glycol antistatic agent and dispersant in anhydrous ethanol to form a mixture A; S02: dissolving polyurethane and silane coupling agent in anhydrous ethanol to form a mixture B; S03: stirring and dissolving the basic resin and the organotin catalyst in propanol, and standing for 3-4 hours; then adding the polyethylene glycol type antistatic agent, boron nitride, and graphene oxide and mixing evenly to form a mixture C; S04: uniformly mixing mixture A, mixture B and mixture C by ultrasonic dispersion, filtering, washing and drying to obtain mixture D; S05: Apply the mixture D to the surface of the photovoltaic module and dry it at room temperature for 14-16 hours to obtain a self-cleaning coating.
7. The method for preparing a dustproof self-cleaning coating according to claim 6, characterized in that: The step S03 comprises: A. Stir and dissolve the basic resin and organotin catalyst in propanol and let stand for 3 hours; B. Then, add polyethylene glycol antistatic agent, boron nitride and graphene oxide at a concentration of 40-50 mg / mL to step A, stir for 4-6 hours, separate the solid and liquid, and dry to form a mixture C.
8. The method for preparing a dustproof self-cleaning coating according to claim 7, characterized in that: The preparation of the graphene oxide comprises the following steps: Graphene is added to a mixture of hydrogen peroxide and sodium borate, and reacted for 20 to 60 minutes in an ice bath at a temperature below 10-15° C. to obtain preliminary graphene oxide. The temperature is then raised to 30° C., potassium permanganate is added, and reacted for 20 to 50 minutes to obtain graphene oxide.
Citation Information
Patent Citations
PETT lining technology
CN106273413A
Pipeline lined with polytetrafluoroethylene
CN106280150A
Preparation method of boron nitride-graphene oxide composite anticorrosive filler
CN106987164A
Conductive self-cleaning coating for solar panels and preparation method of conductive self-cleaning coating
CN109337530A
Chemical equipment pipe and pipe processing technology thereof
CN109595402A